Update breast cancer 2021 part 4 - Prevention and early stages = Update Mammakarzinom 2021 Teil 4 - Prävention und frühe Krankheitsstadien - Thomssen, Christoph; Fehm, Tanja; Stickeler, Elmar; Fasching, Peter A.; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lüftner, Diana; Müller, Volkmar; Schütz, Florian; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
This past year has seen new and effective options for further improving treatment outcome in many patients with early-stage breast cancer. Patients with hormone receptor-positive disease benefited significantly from the addition of the CDK4/6 inhibitor abemaciclib to endocrine adjuvant therapy. In triple-negative disease, data were presented for two treatment regimens. Patients with advanced disease (stage 2 and 3) benefit from neoadjuvant treatment with the immune checkpoint inhibitor pembrolizumab in combination with standard chemotherapy, regardless of PD-L1 expression. When neoadjuvant therapy has failed to achieve the desired remission in BRCA1 and BRCA2 mutations, the administration of the PARP inhibitor olaparib has demonstrated an impressive response. Other data address translational issues in HER2-positive breast cancer and neoadjuvant therapy approaches with the oral SERD giredestrant and the PARP inhibitor talazoparib. This review presents and analyses the findings of this yearʼ s most important study outcomes.